Eplerenone improves endothelial function and arterial stiffness and inhibits Rho-associated kinase activity in patients with idiopathic hyperaldosteronism: a pilot study. Issue 5 (May 2019) - Kishimoto, Shinji; Oki, Kenji; Maruhashi, Tatsuya; Kajikawa, Masato; Matsui, Shogo; Hashimoto, Haruki; Takaeko, Yuji; Kihara, Yasuki; Chayama, Kazuaki; Goto, Chikara; Aibara, Yoshiki; Yusoff, Farina Mohamad; et al.
Abstract : Objective: Primary aldosteronism is one of the most common cause of secondary hypertension. It is well known that the incidence of cardiovascular events is higher in patients with primary aldosteronism than in patients with essential hypertension. In a previous study, we showed that aldosterone-producing adenoma is associated with vascular function and structure. The aim of this study was to evaluate the effects of eplerenone on vascular function in the macrovasculature and microvasculature, arterial stiffness and Rho-associated kinase (ROCK) activity in patients with idiopathic hyperaldosteronism (IHA). Methods: Vascular function, including reactive hyperemia index (RHI), flow-mediated vasodilation (FMD) and nitroglycerine-induced vasodilation (NID), arterial stiffness including brachial–ankle pulse wave velocity (baPWV) and brachial intima–media thickness (IMT) and ROCK activity in peripheral leukocytes were measured before and after 12 weeks of treatment with eplerenone in 50 patients with IHA. Results: After 12 weeks, eplerenone decreased the aldosterone renin ratio but did not alter SBP and DBP. Eplerenone treatment increased log RHI from 0.56 ± 0.25 to 0.69 ± 0.25 ( P < 0.01) and NID from 12.8 ± 5.8 to 14.9 ± 6.9% ( P = 0.02) and it decreased baPWV from 1540 ± 263 to 1505 ± 281 ( P = 0.04) and ROCK activity from 1.20 ± 0.54 to 0.89 ± 0.42 ( P < 0.01), whereas there was no significant change in FMD (increase from 4.6 ± 3.4 to 4.6 ± 3.6%, P = 0.99) or brachial IMT (decrease from 0.28 ± 0.07 to 0.28 ± 0.04 mm, P = 0.14). Conclusion: Eplerenone improves microvascular endothelial function, vascular smooth muscle function, arterial stiffness and ROCK activity in patients with IHA. Clinical Trial Registration Information: URL for Clinical Trial: http://UMIN ; Registration Number for Clinical Trial: UMIN000003409